Efficiency determinants of Malaysian public Waqf in a dynamic environment / Hazriah Hasan - Hasan, Hazriah (Institute of Graduate Studies, UiTM, 2017)
Managerial efficiency is all important in financing a not-for-profit foundation. Waqf or endowment is among one of the Islamic financial institutions set up for the sole intention to serve as a catalyst for economic growth and development of Muslims. In Malaysia, every state does its own Waqf department under the organization of State Islamic Religion Councils (SIRCs). As sole single trustees of Waqf funds, SIRCs are responsible to do all the bodily processes and transactions done for the development and aggregation of finances as easily as to invest and administer the revenues from the finances. This research is divided into three analyses. Firstly, this research did an extensive measurement using the Data Envelopment Analysis (DEA) to investigate the dynamic efficiency performance of Waqf Departments in Malaysia. This research breaks the efficiency measurement into three sections; i. Dynamic DEA analysis to cover the Technical Efficiency (TE), Pure Technical Efficiency (PTE) and Scale Efficiency (SE) in static CRS efficiency measurement, VRS efficiency measurement, dynamic CRS efficiency measurement with two approaches of input orientation and output orientation. ii. Two-stage DEA measurement to measure both Waqf collection and Waqf distribution functions. The Two-stage DEA separates the collection function from the distribution function. iii. Waqf Management Efficiency (WME) Index that measured by DEA Malmquist Total Factor Productivity Index. This WME Index is to detail on the efficiency changes that comprises of Efficiency Change, Technical Change, Productivity Change, Scale Efficiency Change and Total Factor Productivity Change…